Pneumococcal vaccination reduced the risk of acute otitis media: Cohort study - Hasegawa, Junko; Mori, Mitsuru; Showa, Satoko; Matsushima, Aiko; Ohnishi, Hirofumi; Tsugawa, Takeshi; Yoto, Yuko; Tsutsumi, Hiroyuki (Pediatrics international, 2015)
Background Seven‐valent pneumococcal conjugate vaccine (PCV7) was introduced to Japan in 2009, and after that invasive pneumococcal disease has gradually decreased. There are few data, however, on the effectiveness of PCV7 against acute otitis media (AOM) in Japan. Methods From 10 daycare centers in Sapporo, Japan, 614 parents participated in the survey. Each parent reported whether their child subject had received one or more doses of PCV7, and, if so, the exact dates of receiving PCV7 were verified by reviewing their maternal and child health handbooks marked by a pediatrician. AOM was diagnosed by otorhinolaryngologist or pediatrician. Cox's proportional hazard model was used for calculating the hazard ratio (HR) of AOM incidence reduced by PCV7 inoculation. Results Inoculation of PCV7 significantly reduced the risk of AOM (crude HR, 0.63; 95%CI: 0.50–0.79). Adjusting for potentially confounding variables reduced the risk further (adjusted HR, 0.32; 95%CI: 0.23–0.44). On stratification by subject age on 30 April 2012, PCV7 was significantly associated with a reduced risk of AOM in both infants <3 years old, and in children ≥3 years. Conclusion PCV7 is effectiveness in reducing the risk of AOM both in infants <3 years old, and in young children ≥3 years in Japan.